Three new species of the genus Argyresthia Hübner, [1825] from Guatemala, with notes on host plant evolution and Nearctic taxa (Lepidoptera: Argyresthiidae) - Gorneau, Jacob A.; Jones, Loren D.; Monzón-Sierra, José; Dombroskie, Jason J. (SHILAP Revista de lepidopterología, 2023)
Neotropical species of the genus Argyresthia Hübner, [1825] represent a reservoir of undescribed biodiversity and are the most poorly known members of this cosmopolitan genus. From a series of Guatemalan material, three new species are described: Argyresthia quetzaltenangonella Gorneau & Dombroskie, sp. nov., Argyresthia guatemala Gorneau & Dombroskie, sp. nov., Argyresthia iridescentia Gorneau & Dombroskie, sp. nov., representing the first Neotropical species to be described in over a century, and the first from Central America. A phylogeny is inferred using the barcode gene cytochrome c oxidase subunit I (COI), representing an initial foray into the internal relationships of the family. For species with known host plants and available molecular data, a stochastic character mapping analysis was conducted to estimate character states at internal nodes. Furthermore, this phylogeny allows for preliminary insights into the monophyly of the subgenus Blastotere Ratzeburg 1840. Systematic work on Argyresthia remains particularly salient as species in the genus run the gamut from being pests to being considered extinct. Furthermore, notes are provided regarding the status of select Nearctic species, such as the ongoing confusion in North America between Argyresthia goedartella (Linnaeus, 1758) and A. calliphanes Meyrick 1913. Focusing taxonomic efforts on Argyresthia of the Neotropics will lay the foundation for future work regarding biodiversity, ecology, and biogeography of the family.